PENGARUH BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PT. TELKOM KANTOR WILAYAH PALEMBANG - Debitri Primasheila; agustina hanafi; supardi A.Bakri (JEMBATAN, 2017)
This study aims to find out the effect of the organizational culture on job satisfaction of the employees of PT Telkom of Palembang Regional Office. The population was all employees of PT Telkom of Palembang Regional Office with the total number of 154 people and the number of the sample was 61 respondents taken using simple random sampling technique. The method of data collection used a questionnaire for getting the primary data. To support the primary data, the secondary data were collected using interview and documentation technique. The method of data analysis used simple linear regression. The data were processed using the application of Statistical Product and Service Solution (SPSS) Version 20. The result of the study shows that the organizational culture significantly influences the job satisfaction of the employees of PT Telkom of Palembang Regional Office. Keywords: Organizational Culture, Job Satisfaction